Sarcopenia and Low Back Pain in Older Adults - Carvalho do Nascimento, Paulo Roberto (Université d'Ottawa / University of Ottawa, 2022)
The risk of having a disability increases with advancing age and as the life expectancy is growing worldwide, the number of people living with disability is expected to increase, as well as the number of years lived with disability. Low back pain and sarcopenia are health problems that present a higher prevalence with aging. While low back pain is a symptom, sarcopenia is considered a geriatric syndrome. However, both issues constitute a significant health burden in older adults. Although there are many research studies investigating low back pain, the participation of older adults is often missing from these studies, preventing the generalization of the findings to this population, and leaving some questions unanswered. On the other hand, sarcopenia is a new research field with gaps to fill and flaws to correct. Questions related to low back pain management in older adults, the inclusion of this population in clinical trials, the presence of association between sarcopenia and low back pain and questions pertaining the diagnosis and measurement of sarcopenia have yet to be fully addressed by researchers. The broad aim of this thesis therefore was to contribute to a better understanding concerning low back pain and sarcopenia in older adults by performing studies in these key research areas. Different interventions are presented in clinical practice guidelines for the treatment of low back pain. However, these recommendations are based on clinical trials investigating young and middle-aged adults and as a result, the recommendations do not encompass older adults. Therefore, a systematic review was performed with the objective of assessing the effectiveness of interventions for low back pain in older adults ≥ 60 years (Chapter 3). Eligible studies were identified via searches in Medline, EMBASE, CINAHL, LILACS, PEDro, and Cochrane CENTRAL. A total of 18 randomized controlled trials fulfilled the eligibility criteria and the results from eight trials were pooled in a meta-analysis to test the effectiveness of complementary health approaches (i.e., manual therapy, acupuncture, mindfulness, yoga). Evidence about interventions to manage non-specific low back pain in older adults was found to be weak. Very low to moderate quality evidence showed that complementary health approaches, percutaneous electrical nerve stimulation, education, exercise, or pharmacological agents did not produce a clinically significant reduction in pain and disability at short and intermediate terms compared to sham, usual care, or minimal intervention. Interventions were often not well described and the risk of bias was moderate (average of 6.4 on the 10-point PEDro Scale (SD = 1.44)). Evidence about interventions for non-specific low back pain in older adults is limited and new studies are highly likely to change these results. Participation of older adults in clinical trials pertaining to the management of low back pain has been limited. Usually, the exclusion of older adults from clinical trials is based solely on an arbitrary age limit. Therefore, an investigation concerning the potential increased inclusion of older adults in upcoming clinical trials was conducted (Chapter 4). Chapter four presents an analysis of the International Clinical Trial Registry Platform database from the World Health Organization performed to verify the participation of older adults in registered clinical trials. A total of 167 clinical trial protocols for low back pain with registration dates from January 2015 through November 2018 were planning to recruit participants older than 65 years. However, only five registered trials (2.99%; pooled sample = 169 participants) were designed to target this population specifically. The exclusion of older participants was not formally justified and imposed through an arbitrary upper-age limit in 93.6% of the protocols. Most studies planning to include older adults were interested in pharmacologic interventions, devices/technology, and physical rehabilitation, and were to be carried out in developed regions. However, older adults with low back pain will continue to be under-investigated in clinical trials for low back pain in the near future. Although a slight increase in the participation of older adults in clinical trials was observed, the improvement is small and some questions still need an answer. Therefore, a survey investigating whether researchers recognize the exclusion of older adults from clinical trials, its impact, and justifications to support this exclusion was realized (Chapter 5). All attendees of the 2017 International Back Forum were invited by email to answer an electronic survey about their opinions regarding participation of older adults in clinical trials for low back pain. Approximately 90% of those who answered the questionnaire were engaged with back research, with more than a half having done or doing a clinical trial for low back pain. Most of the respondents believed that older people are excluded from clinical trials for low back pain and that exclusion based solely on age is not justifiable. About two thirds of the respondents reported that the exclusion of older people from clinical trials can impose a barrier in offering evidence-based interventions to this population. More researchers are planning to include older adults in their current/future trials compared to their previous work. An increase in the investigation of older adults in clinical trials is expected in the future which may optimize the development of evidence-based interventions for this population. As early evidence suggests an association between sarcopenic markers and low back pain, the association between the diagnosis of sarcopenia and low back pain still needs to be investigated (Chapter 6). Therefore, a study investigating the association between sarcopenia using different diagnosis criteria and low back pain in older adults was performed. Data from 12,646 older adults (50.1% men, 49.9% women) ≥ 65 years of age that participated in the Canadian Longitudinal Study on Aging (CLSA) were analyzed. The prevalence of low back pain in the past 12 months as well the prevalence of sarcopenia assessed through different definitions, and the number of comorbidities and depressive symptoms were included in the analysis. Associations between sarcopenia, comorbidities and lifestyle factors with low back pain were examined using multivariate logistic regressions. Prevalence of low back pain was 16.3% and the prevalence of sarcopenia varied among sarcopenia definitions and the presence of low back pain. Participants with low back pain had higher prevalence of pre-sarcopenia and sarcopenia compared to those without low back pain based on the International Working Group on Sarcopenia (x2 = 20.25, p < 0.001) and the Foundation National Institute of Health definitions (x2 = 13.83, p < 0.001). The odds of having low back pain was higher among those with sarcopenia based on the Foundation National Institute of Health criterion (OR 1.28, 95%CI 1.0-1.64). These results suggest that sarcopenia may influence low back pain in older adults and future studies should consider to test whether the association between sarcopenia and low back pain is causal. Current clinical practice guidelines recommend to divide patients with low back pain in specific subgroups to provide a targeted intervention. However, despite older adults presenting specific age-related characteristics that could classify them as a subgroup, this population has been neglected. Sarcopenia is a muscle disease affecting older adults and is diagnosed with the presence of a reduction in muscle strength and muscle quantity/quality. Although low back pain has been shown to be associated with muscle dysfunction, the role of sarcopenia in relation to low back pain is unknown. An experiment comparing sarcopenic markers (grip strength and gait speed), muscle activity and elasticity between older adults with and without chronic low back pain was conducted (Chapter 7). The anticipatory activity of transversus abdominis muscle during the rapid arm abduction test, transversus abdominis muscle elasticity, grip strength and gait speed were collected from a group of older adults (≥ 60 years) with chronic low back pain (≥ 3 months) and the results compared with a control group of matched older adults without low back pain. Participants with chronic low back pain presented with a reduction in the sarcopenic markers compared with the controls: grip strength (mean difference (MD) = 5.3Kg, 95%CI = 1.5-9.0, p = 0.006), gait speed (MD = 0.21m/s, 95%CI = 0.10-0.31, p<0.001), as well as a delay in activation of transversus abdominis (p = 0.002). A delay in transversus abdominis muscle activation, and a reduction in muscle strength and gait speed were observed in older adults with chronic low back pain compared to subjects without back complaints. These findings show an association between muscle dysfunction and chronic low back pain in older adults. Although the definition of sarcopenia was recently updated establishing muscle strength as the key criteria surpassing the role of muscle mass, there remains confusion regarding its diagnosis and the comparison of estimates is problematic. Therefore, a systematic review assessing how sarcopenia is measured and defined in population-based studies was performed. Chapters 8 and 9 describe the protocol of a systematic review and the full systematic review respectively. The databases Medline, EMBASE, CINAHL, Web of Science (Core Collection), and Google Scholar were searched for observational population-based studies reporting prevalence of sarcopenia in community dwelling older adults. Descriptive statistics were used to present data pertaining to sarcopenia definition and measurement tools, and the quality-effects model for meta-analysis of pooled prevalence. Results found seven different operational definitions of sarcopenia and a variety of measurement tools applied to assess the sarcopenic markers: muscle mass, muscle strength and physical performance. The prevalence of sarcopenia varied between the definitions, with general estimates ranging from 5% based on the European Working Group on Sarcopenia in Older People (EWGSOP1) criterion to 17% with the International Working Group on Sarcopenia criterion. The use of different measurement tools to assess muscle mass, strength and physical performance resulted in variations within definitions ranging from 1 to 7%, 1 to 12% and 0 to 22%, respectively. The criteria used to define sarcopenia, as well as the measurement tools used to assess sarcopenic markers has an influence in the prevalence of sarcopenia. The establishment of a unique definition for sarcopenia, the use of methods that guarantee an accurate evaluation of muscle mass, and the standardization of measurement tools are necessary to allow a proper diagnosis and comparison of sarcopenia prevalence among populations.
Keywords: Sarcopenia; Low back pain; Epidemiology; Muscular atrophy; Ageism; Rehabilitation; Elastography; Spine; Older adults; Qualitative research; Quantitative research; Systematic review